2004
DOI: 10.1158/0008-5472.can-03-2301
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Hypoxia-Induced Tumor Cell Death In vitro and Radiation Therapy In vivo by Use of Small Interfering RNA Targeted to Hypoxia-Inducible Factor-1α

Abstract: Hypoxia-inducible factor-1␣ (HIF-1␣) is an important transcriptional factor that is activated when mammalian cells experience hypoxia, a tumor microenvironmental condition that plays pivotal roles in tumor progression and treatment. In this study, we examined the idea of downregulating HIF-1␣ in tumor cells for therapeutic gain. We show that the expression levels of HIF-1␣ can be significantly attenuated by use of the recently established small interfering RNA technology in combination with adenovirus-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 16 publications
6
71
0
Order By: Relevance
“…The underlying molecular mechanism involves markedly reduced expression of DNA-PKcs, Ku80 and Ku70, three members of the DNA-dependent protein kinases (DNA-PK), in HIF-1 α -deficient MEFs. Our data were supported by a large number of studies that demonstrated reversal of radio-and chemoresistance by targeting HIF-1 α in various tumor types (Zhang et al , 2004 ;Moeller et al , 2005 ;Williams et al , 2005 ;Brown et al , 2006 ;Li et al , 2006a,b ;Song et al , 2006 ;Sasabe et al , 2007 ). For example, Li et al (2006a,b) showed that the knockdown of HIF-1 α in breast carcinoma cells repressed G 0 /G 1 -phase accumulation and relieved S-phase block, thereby increasing sensitivity to chemotherapy and attenuating tumor growth (Li et al , 2006a,b ).…”
Section: Targeting Hif To Improve Cancer Therapysupporting
confidence: 78%
“…The underlying molecular mechanism involves markedly reduced expression of DNA-PKcs, Ku80 and Ku70, three members of the DNA-dependent protein kinases (DNA-PK), in HIF-1 α -deficient MEFs. Our data were supported by a large number of studies that demonstrated reversal of radio-and chemoresistance by targeting HIF-1 α in various tumor types (Zhang et al , 2004 ;Moeller et al , 2005 ;Williams et al , 2005 ;Brown et al , 2006 ;Li et al , 2006a,b ;Song et al , 2006 ;Sasabe et al , 2007 ). For example, Li et al (2006a,b) showed that the knockdown of HIF-1 α in breast carcinoma cells repressed G 0 /G 1 -phase accumulation and relieved S-phase block, thereby increasing sensitivity to chemotherapy and attenuating tumor growth (Li et al , 2006a,b ).…”
Section: Targeting Hif To Improve Cancer Therapysupporting
confidence: 78%
“…Real-time PCR analysis of HIF-1α and VEGF mRNA levels was performed using the iScript TM One-step RT-PCR Kit with SYBR® Green, according to the manufacturer's instructions. The following primers were designed for real-time PCR: HIF-1α, forward 5′-GTTTACTAAAGGACAAGTCACC-3′ and reverse 5′-TTCTGTTTGTTGAAGGGAG-3′ [19] ; VEGF, forward 5′-TCTACCTCCACCATGCCA AGT-3′ and reverse 5′-GATGATTCTGCCCTCCTCCTT-3′ [20] ; β-actin, forward 5′-TCAAGATCATTGCTCCTCCTG-3′ and reverse 5′-CTGCTTGCTGATCCACATCTG-3′ [21] . All the primers were synthesized by Shanghai Sangon Biological Engineering Technology and Services Co, Ltd (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The adaptational response of tumour cells against hypoxia is thought to be mainly mediated by HIF-1a, which transactivates a number of target genes leading to metabolic adaptation, angiogenesis, invasion/metastasis and apoptosis resistance (Semenza, 2003). Recent studies reported that interfering treatments targeting HIF-1a, such as antisense or siRNA, induced apoptosis of human tongue squamous carcinoma cells in vitro (Zhang et al, 2004a) and inhibited tumour growth in human cervical and colon adenocarcinoma cells in vivo (Zhang et al, 2004b). In this experiment, we demonstrated that the reduction of the constitutive level of HIF-1a by an antisense HIF-1a oligonucleotide markedly increased the number of apoptotic cells ( Figure 6C).…”
Section: Tas106 Radiosensitises Tumour Cells Through Hif-1a Inhibitiomentioning
confidence: 99%